Towards a digital platform for performance management and systemic improvement of education systems: evidence from Morocco - Hind Benlhabib; Abdelaziz Berrado (Discover Education)
Abstract The conventional perception of Information Systems (IS) in educational systems, focused on improvement, often confines its role to the technical management of dashboards and performance indicators. Its transformative nature has, however, a profound impact at different levels: individual, institutional and even systemic. Thus, education systems' improvement initiatives having grown in complexity and urging systemic approaches, position IS at their core, assuming a pivotal role. This work strives to provide countries adopting performance management initiatives with a digital platform architecture for maximizing the potential of IS in educational reform. Reflecting on the state of the art in the use of information technologies in the systemic transformation of organizations, the design of our digital platform is drawing on TOGAF framework. For the development of strategic and business aspects, we draw on recent empirical studies that examine performance issues in education systems. Rooted in the theory of systemic improvement, four drivers of transformation have been identified. These drivers underpin the fundamental components of the digital platform. The Moroccan case study is used to illustrate functional and technical aspects of the platform but highlighted at the same time the major turning point that Morocco’s education policy is currently undergoing in terms of systemic improvement, and the potential of IS in enabling this transformation. In summary, this work introduces the concept of Performance Management and Systemic Improvement of Education (PMSIE) through a digital platform. The applicability of this concept in transforming education systems paves the way for new research avenues, including adaptability, productivity and data governance.